2016
DOI: 10.1073/pnas.1605482113
|View full text |Cite
|
Sign up to set email alerts
|

CO 2 -fixing one-carbon metabolism in a cellulose-degrading bacterium Clostridium thermocellum

Abstract: Clostridium thermocellum can ferment cellulosic biomass to formate and other end products, including CO 2 . This organism lacks formate dehydrogenase (Fdh), which catalyzes the reduction of CO 2 to formate. However, feeding the bacterium 13 C-bicarbonate and cellobiose followed by NMR analysis showed the production of 13 C-formate in C. thermocellum culture, indicating the presence of an uncharacterized pathway capable of converting CO 2 to formate. Combining genomic and experimental data, we demonstrated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 40 publications
1
48
0
1
Order By: Relevance
“…The overexpression of ECM proteins, combined with the obstruction of their degradation, contributes to the accumulation of the ECM, eventually leading to tissue fibrosis [34-38]. Moreover, Kim et al found that the ECM can regulate EMT during pulmonary fibrosis [39]. Using western blotting analysis, we proved that TGF-β1 caused an increase in the level of collagen I, a major ECM protein (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…The overexpression of ECM proteins, combined with the obstruction of their degradation, contributes to the accumulation of the ECM, eventually leading to tissue fibrosis [34-38]. Moreover, Kim et al found that the ECM can regulate EMT during pulmonary fibrosis [39]. Using western blotting analysis, we proved that TGF-β1 caused an increase in the level of collagen I, a major ECM protein (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…Synthetic PFOR is the key enzyme of the autotrophic fixation by the Wood-Ljungdahl pathway in acetogens (Furdui and Ragsdale, 2000). After our publication of the synthetic activity of PFOR in T. neapolitana (d' Ippolito et al, 2014), Xiong et al (2016) have reported a similar mechanism in Clostridium thermocellum. In this work, the authors report assimilation of CO 2 during cellobiose metabolism with fixation of over 40% of labeled carbon in PYR that derives from PFOR-dependent synthesis.…”
Section: Discussionmentioning
confidence: 96%
“…2 | MATERIALS AND METHODS 2.1 | Plasmid and strain construction C. thermocellum DSM1313-derived mutant Δhpt, also referred to as KJC315 (Xiong et al, 2016), was the parental strain in this study. The gene hpt (clo1313_2927) encodes for hypoxanthine phosphoribosyl transferase, which was used for counter-selection in the presence of 8azahypoxanthine.…”
mentioning
confidence: 99%